Holy Shepherds in Orthodox Art. An Unsuccessful Attempt to Create Patron Saints of Everyday Works - Grotowski, Piotr Ł. (Vox Patrum, 2026)
Herding was an important component of the medieval Mediterranean society economy. Peasants involved in this activity needed celestial protectors, whose support could facilitate their life and daily duties. Among the crowd of martyrs, they found saints - such as Mamas, Tryphon, Blasios of Caesarea - who according to their Lives occupied with herding. From the mid-eleventh century one can observe the firsts attempts to create specific iconography of the group. Their ties with agriculture were underlined by the introduction of attributes such as a shepherd’s crook and subsequently the animal (usually lamb, goat or an ox) depicted in the saint’s hand. Such kind of images gained some popularity, especially in rural communities of the insular milieu. However, Holy Shepherds as a group never reached official ecclesiastical acceptance and in time faded as a separated category. An exception was St. Mamas, whose images compounded of oriental (a lion) and herding (lamb or goat) motifs remained popular, especially in Cyprus, where his sanctuary (Morphou) was also created. In turn in Russian folk tradition appeared beliefs that associated Sts. Florus and Laurus (originally stonemasons) with horses. They found reflection in art in the form of the icons on which Archangel Michael gives the reins of stallions to the brothers as a sign of their supernatural power over these animals. This vernacular iconography was also rejected by the Church authorities and the Holy Synod of 1722 condemned such depictions as unorthodox.